2004
DOI: 10.1007/s00381-004-1068-2
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty in children

Abstract: In this series, the use of the patients' own craniectomised flap had a low infection rate, and was mainly seen in patients who had bilateral flaps re-implanted soon after removal. There were no complications arising from the use of split calvarial and allograft material. Use of autologous implant material should be preferred whenever possible due to obvious resource and biological advantages, and can even be re-implanted if infected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 16 publications
0
81
1
2
Order By: Relevance
“…12 Of the 14 patients in this study who underwent a total of 16 cranioplasties with stored bone, 12 had previously undergone decompressive craniectomy. Details regarding complications occurring in the decompressive craniectomy subset are not available, although the authors state that the indication for craniectomy had no effect on the rate of resorption or infection determined using a linear regression model.…”
Section: Methods Of Storagementioning
confidence: 99%
See 4 more Smart Citations
“…12 Of the 14 patients in this study who underwent a total of 16 cranioplasties with stored bone, 12 had previously undergone decompressive craniectomy. Details regarding complications occurring in the decompressive craniectomy subset are not available, although the authors state that the indication for craniectomy had no effect on the rate of resorption or infection determined using a linear regression model.…”
Section: Methods Of Storagementioning
confidence: 99%
“…4,8,12,14 Articles by Grant et al 8 and Josan et al 12 state that the authors found no significant correlation between time to reimplantation and postcranioplasty complication. However, neither paper provides details about time to reimplantation or the specific effect that this factor has on complication rate in either the univariate or multivariate analysis.…”
Section: Timing Of Cranioplastymentioning
confidence: 97%
See 3 more Smart Citations